Obsessive-compulsive disorder: its what and how from an Islamic perspective - Abdul Razak, Abdul Latif (Kolej University Islam Sultan Azlan Shah, 2014)
Obsessive–Compulsive Disorder (OCD) is a type of anxiety in which a person suffers from obsessions i.e. unwanted intrusive ideas which recur to the person persistently; and compulsions i.e. behaviours that a person feels compelled to perform repeatedly in a ritualistic manner with the aim of relieving the anxiety from the unpleasant obsessive thoughts. Although compulsion and obsession are common, once the individual experiences excessive discomfort, then he or she would be diagnosed as a patient of this disorder. Most of the research outputs on this disorder are based on secular and irreligious perspectives. Thus, this research aims at religiously diagnosing its root causes and exploring its remedies based the Qur’an and Sunnah and the works of early Muslim scholars. The finding shows that this disorder, its etiology and treatment, has been extensively discussed in many works of early Muslim scholars that can be benefited by modern psychotherapists.